Drosophila Ovarian Stem Cell Establishment is Regulated by Nuclear Hormone Receptor ftz-f1 - Berghout, Hanna E. (East Carolina University, 2017)
Stem cells are a fundamental underpinning of tissue biology. Loss of the self-renewing function of stem cells leads to conditions such as infertility and tissue wasting. Stem cells integrate a variety of signals to maintain their fate and proliferative capacity. Although intrinsic and local cues are well studied, less is known about how extrinsic signals, such as hormones, affect stem cell fate and function. The highly characterized Drosophila melanogaster steroid hormone ecdysone regulates germline stem cell (GSC) proliferation and self-renewal, as well as oogenesis and metamorphosis. Though many genes, including nuclear hormone receptor ftz transcription factor 1 (ftz-f1), are thought to be targets of ecdysone signaling, it is unclear how these targets impact GSC fate and function. To explore the role of ftz-f1 in ovarian stem cells, we used the UAS-GAL4 system and RNA interference (RNAi) to reduce ftz-f1 function specifically in germ cells or surrounding somatic cells. We demonstrate that ftz-f1 is intrinsically required for the establishment of the proper number of GSCs during development. Reduced ftz-f1 function in germ cells leads to a significant decrease in average number of GSCs. During larval stages, ftz-f1 depleted ovaries contain a number of PGCs located significantly further away from the terminal filament stacks. Our results also suggest that ftz-f1 is required in ovarian somatic cells during development for proper movement of germ cells out of the germarium in adult stages. Taken together, we suggest ftz-f1 function during juvenile stages is critical for the establishment of GSCs and development of their progeny.
Keywords: establishment; primordial germ cells; development; niche; Hormone receptors; Drosophila melanogaster; Stem cells; Ecdysone